2014
DOI: 10.1186/1471-2393-14-81
|View full text |Cite
|
Sign up to set email alerts
|

An inexpensive device to treat postpartum hemorrhage: a preliminary proof of concept study of health provider opinion and training in Nepal

Abstract: BackgroundObstetric hemorrhage remains the leading cause of maternal mortality in resource limited areas. An inexpensive pneumatic anti-shock garment was devised of bicycle tubes and tailored cloth which can be prepared from local materials in resource-limited settings. The main purposes of this study were: 1) to determine acceptability of the device by nurses and midwives and obtain suggestions for making the device more suitable for use in their particular work environments, 2) to determine whether a three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…An initial group of 58 providers was trained in 2010 to use the prototype bicycle tube device. These were used 10 times with good results, as previously reported 17 . Providers continued to use the device after the initial study and, in 2017, an additional 74 providers were trained using the Ball and Binder version.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…An initial group of 58 providers was trained in 2010 to use the prototype bicycle tube device. These were used 10 times with good results, as previously reported 17 . Providers continued to use the device after the initial study and, in 2017, an additional 74 providers were trained using the Ball and Binder version.…”
Section: Methodsmentioning
confidence: 85%
“…The prototype three‐compartment device was used 28 times in Nepal in addition to the 10 cases previously reported 17 . Devices with only an abdominal compartment were used 40 times in Nepal (10 using the soccer ball) and 28 times in PNG (all using the soccer ball).…”
Section: Resultsmentioning
confidence: 99%
“…The top 25 global EM articles for 2014 are listed in Table . The complete database of all 477 global EM articles for 2014, as well as full summaries and critical analyses of the top 25 global EM articles of 2014 can be found in Data Supplements S1 and S2 (available as supporting information in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Postpartum hemorrhage is the leading cause of maternal mortality worldwide and a concern for public health practitioners and acute care providers alike, particularly in areas where definitive obstetric care may be delayed or unavailable. Kerr et al . report on a proof‐of‐concept study evaluating a novel, inexpensive, pneumatic antishock garment made of bicycle tire tubes and locally available cloth for the treatment of postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middleincome countries, postpartum haemorrhage mortality is high (5,8). Previous studies have shown that treatment is most effective if started promptly (9). In 80% of cases of postpartum haemorrhage, women receive substandard care (10), underestimation of blood loss, delayed diagnosis and management of haemorrhage treatment failures (11), lack of easy-to-use local protocols (active management of the third stage of labour), lack of adequate education and training, and poor communication.…”
Section: Introductionmentioning
confidence: 99%